Role of Vγ9vδ2 T lymphocytes in infectious diseases - Gay, Laetitia; Mezouar, Soraya; Cano, Carla; Frohna, Paul; Madakamutil, Loui; Mège, Jean-Louis; Olive, Daniel (Frontiers in Immunology, 2022)
The T cell receptor Vγ9Vδ2 T cells bridge innate and adaptive antimicrobial immunity in primates. These Vγ9Vδ2 T cells respond to phosphoantigens (pAgs) present in microbial or eukaryotic cells in a butyrophilin 3A1 (BTN3) and butyrophilin 2A1 (BTN2A1) dependent manner. In humans, the rapid expansion of circulating Vγ9Vδ2 T lymphocytes during several infections as well as their localization at the site of active disease demonstrates their important role in the immune response to infection. However, Vγ9Vδ2 T cell deficiencies have been observed in some infectious diseases such as active tuberculosis and chronic viral infections. In this review, we are providing an overview of the mechanisms of Vγ9Vδ2 T cell-mediated antimicrobial immunity. These cells kill infected cells mainly by releasing lytic mediators and pro-inflammatory cytokines and inducing target cell apoptosis. In addition, the release of chemokines and cytokines allows the recruitment and activation of immune cells, promoting the initiation of the adaptive immune response. Finaly, we also describe potential new therapeutic tools of Vγ9Vδ2 T cell-based immunotherapy that could be applied to emerging infections.